Pendampingan Digitalisasi Manajemen Administrasi Sampah Di Desa Kertosari Kecamatan Purwosari Kabupaten Pasuruan - Senja Ike; Indarwati Azizah (LPPM Universitas Yudharta Pasuruan, 2021)
Garbage is the residue of human daily activities and/or natural processes in solid form (Depkes RI, 2008). Garbage has two special types, namely organic waste and inorganic waste. Waste not only has a negative value but also has a positive value if it is managed properly and according to its specifications. Based on the results of observations in Kertosari village, it can be obtained that knowledge about waste is still minimal. This is due to their improper waste management. They say that garbage is just used goods and the only way to deal with it is to get it out of sight, for example by throwing it away or throwing it in a landfill. Therefore, in this case we use the method of direct service to the community, namely by socializing the role of waste banks and helping digitize. The results of this observation, which are based on the potential and problems that exist in Kertosari Village, the application that is considered feasible to be applied at this time is the digitization of the administrative system only. With the reason, so that the administrative system can be more effective and efficient. As for the customer application, it still cannot be implemented because it is constrained by the age of the customer who dominates 50 years and over.